Antilithiatic Activity of Averrhoa bilimbi L. Leaves Ethanol Extract on White Mice (Mus musculus) - Patala, Recky; Ibrahim, Nurlina; Khumaidi, Akhmad (Pharmacology and Clinical Pharmacy Research, 2018)
Nephrolithiasis refers to the formation of urinary calculi in the kidney and urogenital tract. It is associated with impairment of renal function. The leaves of Averrhoa bilimbi L are used empirically to treat abdominal pain, rheumatism, and to reduce kidney disorders symptoms. The aim of this study was to identify antilithiatic activity of ethanol extract of A. bilimbi L. leaves by determining the kidney weight changes and calcium levels in kidney extract of mice using Atomic Absorption Spectrophotometry (AAS) at 422.7 nm. A total of 18 male mice were included and classified into 5 groups, i.e., positive control, negative control, and extract at 16.6; 25; and 33 mg/kg BW.Â  Result showed that the calcium levels of the A. bilimbi L. extract groups were significantly lower than the control group (p<0.05). The most effective dose was 16.6 mg/kg BW. In conclusion, the leaves ethanol extract of A. bilimbi L. possessed antilithiatic activity.Keywords: Averrhoa bilimbi L., antilithiatic activity, calcium levels, kidney stones, renal impairment